UNCLOS and Beyond: Strengthening Maritime Governance through International Legal Frameworks: https://doi.org/10.5281/zenodo.16937200 - Faisal Awais (`, 2025)
The United Nations Convention on the Law of Sea (UNCLOS) is the bedrock of maritime governance, setting out nations’ rights and responsibilities in the use of the world’s oceans. However, given the dynamic nature of global maritime activities, as well as increased environmental, geopolitical, and technological challenges, the current legal framework is not fully equipped to address these challenges and necessitates reconsideration. This paper critically explores to what extent UNCLOS is an effective instrument for modern maritime governance, for example, its ability to resolve transboundary maritime disputes, marine pollution, and the governance of new maritime areas in climate change. This includes the problem areas in which UNCLOS is felt to have insufficient regulatory scope, the challenges of cyber threats against shipping, the exploitation of deep-sea resources, and maritime security in a multi-polar world. The paper analyses its success and gaps in the UNCLOS framework using the comparative analysis of international case law, maritime dispute resolution mechanisms, and regional agreements. Further, it explores the contribution of complementary international organizations to the oversight of the law and operation of the safety of the International Maritime Organization (IMO). This study argues that to address the realities of the modern geopolitical and environmental landscape, maritime governance should take a multi-dimensional approach that integrates UNCLOS with emerging legal principles and regional cooperation models. UNCLOS, however, remains foundational but requires adaptation and supplementation through new legal instruments and intergovernmental collaboration. Finally, this research suggests ways to reform maritime governance to promote sustainable development, environmental conservation, and peaceful navigation. Keywords: UNCLOS, Maritime Governance, Transboundary Disputes, Environmental Conservation, Cyber Threats in Shipping.